Rural Internet Banking Usage : A Study with Special Reference to Idukki District of Kerala - Nirmal Sabu (Research Revolution, 2014)
Internet banking is the latest technological revolution in the banking field. Providing banking services through internet is known as internet banking or virtual banking. Here the researcher has undertaken a study to analyse the usage of online banking facilities by the people in Idukki, a rural district. The research came out with some stricking discoveries. There is a high level of internet banking usage among the people in Idukki district. Here the people mainly use online banking facilities for checking account details and for withdrawals. People in the age group of 15-30 years and 30-45 years are the main users of virtual banking facilities. Although there exist a relationship between educational level of people and internet banking usage i.e, people with degree and above qualification are more using online banking, there exists no relation between gender and internet banking usage i.e, there is no significant variation among men and women in Idukki district in the matter of using internet banking facility.